The Image of Abdulla Avloni in Uzbek Literature - Mansurova Malika Askarovna (International Journal on Integrated Education, 2021)
This article examines the changes in the image of Abdulla Avloni in two stories by Tahir Malik, "Qaldirg‘och” (“Swallow") and later revised and published under the name "Savohil" (“Two banks”), as well as the artistic interpretation of the image of the Jadid writer in the story "Savohil". Theoretical views on the role of historical sources in the creation of the image of the creator are expressed.